DAUN ANGSANA SEBAGAI ALTERNATIF PEMBUATAN KOMPOS DENGAN METODE BIOPORI PADA KONDISI BANJIR TAHUN 2016 - Fariani Pratiwi Putri; Siti Surasri; Sri Mardoyo (GEMA LINGKUNGAN KESEHATAN, 2016)
Surabaya is one of frequently flooded city in Indonesia. The installation of box culvert and Angsana tree planting on the roadside are efforts to minimize flooding. The Angsana tree planting have an impact in the form of excessive leaf waste. Processing the leaves as compost is one effort to reduce the waste. Composting is carried out by using biopori method. Biopori method was chosen since it can be used for composting and serves as a rainwater catchment pit. This is a descriptive study which compare the results of composting by using biopori method on flood conditions and non-flood condition. The results were adjusted to SNI compost. The C/N ratio and composting time are two big considerations in this research. The survey results revealed that the average of C/N ratio was 48.43 before composting, 12.60 after composting in flood conditions and 18.06 in non-flooded condition. The average of temperature, humidity and pH after composting in flood condition were 38℃, 65% and 7 respectively, while after composting at non-flooding were 41°C, 55%, and 7 respectively. The physical condition after composting in flood and non-flood conditions was the same, dark brown-black, ground smell, and soft and easily crushed, yet on flood condition was more friable resembles soil more. The duration needed for the composting process in flood and non-flood condition was the same by 23 days. In flood condition, the shrinkage was faster than in non-flood conditions. In flood condition, the humidity was very high that sawdust was added little by little and the compost was stirred regularly to reduce humidity. Keywords : AngsanaLeaf, Biopori, Compost